Experimental investigations on the surface hardness of synthesized polystyrene/zno nanocomposites - Alam, M.A. (Springer Science and Business Media Deutschland GmbH, 2020)
The addition of inorganic spherical nanoparticles fillers to polymers matrix enables in the enhancement in the polymerâs mechanical properties as well as the addition of new features in the polymer matrix. In the present study, ZnO/polystyrene composite was synthesized by bulk polymerization route and the hardness of composites was studied. The prepared nanocomposites were injected into a compression mold in a compression-molding machine. The prepared test specimen was subjected to Rockwell hardness tests. Further, to ensure proper morphology of nanocomposites, scanning electron microscopy (SEM) and X-ray diffraction (XRD) were carried out. Results revealed that by increasing nano-ZnO up to 0.3, there is a remarkable increment approximately 47 in the hardness. Also, an analysis of variance (ANOVA) has been applied to find the optimal input parameter levels and to analyze the effect of these parameters on hardness. The composite produced is envisioned to have applications as the building blocks for the manufacturing of various automotive parts, sensors, transducers, actuators, UV detectors, and optoelectronic devices. Â© Springer Nature Singapore Pte Ltd 2020.